TCR deep sequencing of transgenic RAG‐1‐deficient mice reveals endogenous TCR recombination: a cause for caution. Issue 6 (24th March 2018) - McGuire, Helen M; Watkins, Thomas S; Field, Matthew; Taylor, Sarah; Yasuyama, Nao; Farmer, Andrew; Miles, John J; Fazekas de St. Groth, Barbara
Abstract: The utility of T‐cell receptor (TCR) transgenic mice in medical research has been considerable, with applications ranging from basic biology all the way to translational and clinical investigations. Crossing of TCR transgenic mice with either recombination‐activating gene (RAG)‐1 or RAG‐2 knockouts is frequently used to generate mice with a monoclonal T‐cell repertoire. However, low level productive TCR rearrangement has been reported in RAG‐deficient mice expressing transgenic TCRs. Using deep sequencing, we set out to directly examine and quantify the presence of these endogenous TCRs. Our demonstration that functional nontransgenic TCRs are present in nonmanipulated mice has wide reaching ramifications worthy of critical consideration. Abstract : The utility of T‐cell receptor (TCR) transgenic mice in medical research has been considerable, with applications ranging from basic biology all the way to translational and clinical investigations. Crossing of TCR transgenic mice with either recombination‐activating gene (RAG)‐1 or RAG‐2 knockouts is frequently used to generate mice with a monoclonal T‐cell repertoire. Using deep sequencing, we set out to directly examine and quantify the presence of endogenous TCRs, demonstrating that functional nontransgenic TCRs are present in nonmanipulated mice, a finding of wide reaching ramifications worthy of critical consideration.